EXPLAINING ACTIONS: THE MODEL OF TELEOLOGICAL EXPLANATION AND ITS DIFFICULTIES (Romanian Journal of Analytic Philosophy, 2025)
The classical model for explaining an action (i.e. for answering the question why someone has done something) usually puts an agent’s desires at the center of the explanation: it is because the agent desired something that the action took place. Collins argues that an appeal to purposes could be a more appropriate explanation, that is, he offers a teleological account of action. In his view, actions could be described as a “compensation” for a perceived lack, for an unaccomplished purpose of the agent, in the way a thermostat or a helmsman brings corrections to a perceived state of affairs. The purpose of my essay is to discuss the difficulties encountered by his proposal. I argue that one needs a clearer account for what may count as “compensatory” in order for the theory to be able to distinguish between a random event, a causal effect and a compensatory action.
Keywords: action; purpose; teleological; explanation; compensatory